An analysis on the translation process of eu acquis communautaire texts from english into turkish - Boy, Hülya (My University, 2017)
Avrupa Birliği (AB), 28 Üye Devlet ve 24 resmi dile sahip çok uluslu ve çok dilli bir yapıdır. Tüm AB vatandaşlarının, Birlik mevzuatına kendi dillerinde erişim hakkına sahip olması dolayısıyla, Birlik vatandaşlarının hukuk önünde eşitliğini korumanın bir göstergesi olarak bütün resmi diller eşit statüye sahiptir. Bu bağlamda, Birlik bünyesi ve sınırları dahilinde kurumsal çok dilliliğin düzgün biçimde işleyişinin sağlanması açısından çeviri vazgeçilmez bir araçtır. AB müktesebatı metinleri çevirisi literatürde özellikle, hedef metinlerin kurumsal ortama ait gerekliliklerden kaynaklı belli bir takım sınırlamalar ile şekillendiği kurumsal çeviri kapsamında ele alınmıştır. Türkiye'de AB katılım öncesi süreçte çeviri, revizyon ve terminoloji çalışmalarının koordinasyonu, Avrupa Birliği Bakanlığı Çeviri Eşgüdüm Başkanlığı (ÇEB) tarafından yürütülmektedir. Bu çalışmada, ilgili koordinasyon süreci temel olarak bu birimden üç personel ile yapılan röportajlar yoluyla toplanmış birinci elden verilere dayanılarak analiz edilmiş ve müktesebat metinlerinin İngilizceden Türkçeye çevirisinde en önemli sorunun, hedef metinlerde alana özgü teknik terminolojinin metin içi ve metinler arası tutarlılığı sağlayacak şekilde doğru ve uygun kullanımı konusunda olduğu sonucuna varılmıştır. Çevirilerde terminolojik tutarlılık ve dilsel birliğin sağlanması amacıyla ÇEB tarafından yürütülen çalışmaların incelendiği bu çalışmada ayrıca seçilmiş üç örnek metne ait çevirilerin, metin gelenekleri ve terminolojik hususlar açısından analizine de yer verilmiştir.

The European Union (EU) is a multinational and multilingual entity with 28 Member States and 24 official languages enjoying equal status as a reflection of safeguarding the Union citizens' equality before law in the sense that all EU citizens have the right to access the Union legislation in their own official languages. In this regard, translation is an indispensable means for ensuring proper functioning of institutional multilingualism within the Union structures and borders. In literature, translation of acquis communautaire texts has been analyzed particularly within the scope of institutional translation in which case target texts are shaped by specific constraints arising from certain requirements of an institutional setting. In the pre-accession process of Turkey to the EU, the coordination of translation, revision, and terminology studies are conducted by Directorate of Translation Coordination (DTC) of Turkish Ministry for EU Affairs. In this study, the related coordination process was analyzed mainly based on first-hand data collected through interviews with three personnel from DTC, and it was concluded that the most important issue in the case of acquis communautaire texts’ translation from English into Turkish is about correct and appropriate use of field-specific technical terminology by ensuring inter- and intra-textual consistency in the target texts. Elaborating on the studies carried out by DTC in addressing this problem to provide terminological consistency and linguistic unity in translations, this study also includes an analysis on three sample translations within the scope of textual conventions and terminological considerations.
Keywords: Acquis Communautaire; Avrupa Birliği; Çeviri Eşgüdüm Başkanlığı; Çok dillilik; Directorate of Translation Coordination; Institutional Multilingualism; Institutional Translation; Kurumsal Çeviri; Kurumsal Çok Dillilik; TermAB; TermAB European Union; Terminological Consistency; Terminolojik Tutarlılık; Topluluk müktesebatı